From What Age Is Mental Rotation Training Effective? Differences in Preschool Age but Not in Sex - Fernández-Méndez, Laura M.; Contreras, María José; Elosúa, M. Rosa (Frontiers in Psychology, 2018)
Currently, there is evidence that spatial skills training leads to an improvement of such skills, although studies with children in the Preschool stage are very scarce. This paper aims to examine the effectiveness of mental rotation (MR) training and sex differences in preschool children. Two experiments were carried out. Experiment 1 included 59 children of 1st course (aged between 3 and 4 years) and Experiment 2, 61 children of 2nd course (aged between 4 and 5 years) of Preschool Education, distributed into control and training groups. The results showed a significant improvement in the mental rotation ability of the training group (measured through a different test than the one used for training) only in the older children, and a tendency toward significance in the younger participants. Moreover, no sex differences in MR or group differences across age groups were found. These results regarding mental rotation training support the malleability of spatial skills approach, particularly in 4-5 year-old preschoolers. This malleability should be enhanced in our educational system, as well as the implementation of educational and social policies that tend towards equality between sexes in the development of spatial skills. This can promote an equitable access to academic careers requiring high spatial skills such as engineering, science, technology or mathematics, in which nowadays women are underrepresented.